The Expansion Mode of Adult Matsucoccus Matsumurae (Hemiptera: Margarodidae) in Pinus Thunbergii (Pinales: Pinaceae) and Pinus Densiflora (Pinales: Pinaceae) Forests in Shandong Province, China - Gao Xing; Chen MengJiao; Zhang Ranran; Qiu Hong; Dai Lulu; Zhao Mingzhen (E3S Web of Conferences)
Understanding the expansion mode of adult Matsucoccus matsumurae Kuwana (Hemiptera: Margarodidae) is important for pest control and management measures. The infection situation, emergence patterns, host selection and aggregation behaviors of females have never been elucidated. In this work, we aimed to complete the expansion mode of adults through field surveys, Y-tube experiments and previous research results. The infection ratios surveys and Y-tube experiments revealed that M. matsumurae prefers to infect Pinus densiflora Sieb (Pinales: Pinaceae) rather than Pinus thunbergii Parl (Pinales: Pinaceae). The P. densiflora surveys suggested that tree height and live crown ratio play important roles in the M. matsumurae host-selection process. The emergence of females was concentrated between 5:00 to 11:00. Females exhibited obvious aggregation behavior on healthy P. densiflora trees, as observed during field surveys, and the female aggregation pheromone probably existed in the Y-tube experiments. These research results illuminate the host choice tendency, emergence pattern and aggregation behavior of females and provide key information for deepening the understanding of the expansion mode of adults. Understanding the expansion mode of females allows the development of new methods for the targeted prevention and control of this species.